Molecular Mechanism of Matrine from Sophora alopecuroides in the Reversing Effect of Multi-Anticancer Drug Resistance in K562/ADR Cells. (22nd November 2019) - Chen, Zhi; Nishimura, Nobuhiro; Okamoto, Takayuki; Wada, Koichiro; Naora, Kohji
Abstract : Multidrug resistance is the main obstacle to current chemotherapies. In this study, we evaluated the reversing effect of matrine, the principal alkaloid derived from Sophora alopecuroides, on chemoresistant leukemia K562/ADR cells. Matrine in a range of the nontoxic concentration was employed in the whole study. IC50 s of cancer medicines were tested using WST-8 assay. Drug export and apoptotic rates were examined using flow cytometry. The mRNA and protein expressions were quantified by quantitative real-time PCR and western blotting, respectively. Our data indicated that matrine had potent reversal properties augmenting cytotoxicity of cancer medicines on K562/ADR cells as well as apoptotic rates induced by doxorubicin. Moreover, matrine inhibited drug-exporting activity and expression of ATP-binding cassette subfamily B member 1 (ABCB1) on both mRNA and protein levels. That might result from inhibited NF-kappa B activation, which also led to restored intrinsic apoptosis. These findings suggest that matrine in the nontoxic concentration can suppress ABCB1 drug transport and facilitate the intrinsic apoptosis pathway through the inhibiting effect on NF-kappa B and has the potential to become an efficient sensitizer for anticancer drug resistance.